2016
DOI: 10.21077/ijf.2016.63.1.37800-15
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight relationship of 57 freshwater fish species from three diverse ecological regimes in India

Abstract: Length-weight relationship and condition factor in 57 freshwater fish species of 19 families and 38 genera from various rivers, and lakes of different climatic zones in India were studied. The estimates (total 67) for the parameter b of the length-weight relationship ranged between 1.422 and 3.917, with a mean value of 2.994. Correlation coefficient was found to be highly significant (r 2 >0.90) in all except for Crossocheilus latius latius, Acanthocobitis botia and Garra lamta. Growth was found to be isometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…LWR parameters of these native fish species reported in this study were also compared with data available in published literature (Table 2) from similar as well as adjacent freshwater ecosystems of India and other countries. A systematic comparison showed relatively higher 'b' values for C. mrigala, S. bacaila and L. rohita from the adjacent arid freshwater river Banas in Rajasthan (Lal et al, 2016). Concomitantly, Ujjania et al (2012) and Balai et al (2017) also reported higher 'b' value for C. mrigala from the river Mahi (3.36) and the Jaisamand Lake (3.02).…”
Section: Resultsmentioning
confidence: 92%
“…LWR parameters of these native fish species reported in this study were also compared with data available in published literature (Table 2) from similar as well as adjacent freshwater ecosystems of India and other countries. A systematic comparison showed relatively higher 'b' values for C. mrigala, S. bacaila and L. rohita from the adjacent arid freshwater river Banas in Rajasthan (Lal et al, 2016). Concomitantly, Ujjania et al (2012) and Balai et al (2017) also reported higher 'b' value for C. mrigala from the river Mahi (3.36) and the Jaisamand Lake (3.02).…”
Section: Resultsmentioning
confidence: 92%
“…Lal et al. () also found that some species exhibited variations in their growth patterns in different habitats in India (rivers and lakes), and related their results to two factors: the influence of preference and availability of suitable habitat conditions. In the present study, it might be related to the availability of suitable habitat conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Since then, EMS/AHPND has affected the production of the Pacific white shrimp in Thailand, dramatically dropping the production to about 217,437 mt/year in 2014. Not only did the outbreak of EMS/AHPND reduce production but also the fear of it hindered recovery [6]. Many shrimp farmers in Thailand have now pulled out of the shrimp farming business, and others have gone back to culturing black tiger shrimp using SPF broodstock produced by private companies.…”
Section: Introductionmentioning
confidence: 99%